Pemberdayaan Perempuan Era Digital Melalui Pelatihan Ecoprint Berbasis E-Learning (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
The digital era opens up new opportunities for women to improve their skills, independence, and role in the creative economy. One potential field is ecoprint, which is a technique to print natural motifs on fabrics that has artistic value and is environmentally friendly. This study aims to describe the implementation of e-learning-based ecoprint training and its impact on women's empowerment. The training method is carried out online via Zoom for virtual face-to-face, Learning Management System (LMS) as a learning center, and digital modules as independent learning materials. The results of the training showed that there was an increase in participants' skills in producing more creative and quality ecoprint products, as well as increasing digital literacy through the use of online learning platforms. E-learning-based ecoprint training has also proven to be effective as a model for women's empowerment in the digital transformation era. The recommendations submitted include increasing internet access, technology assistance, entrepreneurship-based curriculum, and strengthening online communities so that programs can be sustainable and support Indonesia's creative economy.
Keywords: Women's Empowerment; Ecoprint, E-Learning; Digital Literacy; Creative Economy